1991
DOI: 10.1063/1.350172
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence characterization of plasma exposed silicon surfaces

Abstract: The variation of photoluminescence (PL) spectra obtained with silicon exposed to various plasmas as a function of plasma etch treatment conditions is reported. Phosphorus- or boron-doped covering a large range of doping concentrations, Czochralski or float-zone-grown silicon crystals were investigated. The effect of various etching gases on the luminescence spectra as well as the effects of subsequent annealings are reported. Two types of recombination process are observed: (i) The first gives rise of sharp lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Similar broad sub-bandgap PL bands have been described on plasma treated Si [53][54][55], and were attributed to plasma-induced defects at the Si surface. However, the infrared luminescence could only be observed at low temperatures (T < 130 K).…”
Section: Optical Properties Of Ge Nanocrystals Embedded In Zro 2 and supporting
confidence: 73%
“…Similar broad sub-bandgap PL bands have been described on plasma treated Si [53][54][55], and were attributed to plasma-induced defects at the Si surface. However, the infrared luminescence could only be observed at low temperatures (T < 130 K).…”
Section: Optical Properties Of Ge Nanocrystals Embedded In Zro 2 and supporting
confidence: 73%
“…The formation mechanism of C-and G-centers is well established and includes the radiation-induced displacement of a carbon atom to form either a close pair of interstitial oxygen and carbon atoms (C-centers) or carbon substitutional -Si interstitial -carbon substitutional complexes (G-centers). The formation of these defects after CF4 RIE is explained either as a result of bombardment-induced displacement of residual carbon atoms [11] or as a result of carbon implantation from the etching plasma [10]. For SF6 RIE, which does not contain carbon atoms in the etching gas, ion bombardment should be considered as a dominant mechanism of C-and G-centre formation in agreement with Ref.…”
Section: Comparison Of Cf4 and Sf6 Riementioning
confidence: 72%
“…The RIE-induced chemical modifications of the surface are usually investigated by X-ray photoemission spectroscopy (XPS) [4-61, secondary-ion mass spectroscopy (SIMS) [6] and ellipsometry [4,5]. The information about the RIE-induced defects could be obtained using both electrical techniques, such as deep level transient spectroscopy (DLTS) and capacitance-voltage (C-V) measurements [7][8][9], and optical photoluminescence (PL) studies [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The leakage mainly results from the dislocation, stacking faults, and cavities induced by carbon rich polymer formation during the plasma etch and high temperature annealing. [4][5][6][7][8] Conclusions Two types of isolation schemes have been compared by using different gas chemistries. Semi-recessed LOCOS process with low carbon content gas CHF 3 /CF 4 /Ar has demonstrated that junction leakage current is comparable to that with conventional LOCOS.…”
Section: Resultsmentioning
confidence: 99%